Insuficiência hepática aguda na febre amarela: experiência clínico-cirúrgica de um centro transplantador brasileiro no enfrentamento da epidemia do ano de 2018 - Antônio Márcio de Faria Andrade (2023)
Introduction: Acute Liver Failure (ALF) is a serious condition characterized by rapid deterioration of liver function in individuals without pre-existing liver disease, and liver transplantation (LT) is the treatment with the greatest impact in the last decades. Yellow fever (YF) is an infectious disease endemic to forest áreas in Africa and America with high mortality rates. It is a disease with multi-system involvement, but the liver is the most affected organ, which makes ALF a common cause of death. The state of Minas Gerais, in Brazil, was seriously affected by a serious YF epidemic between June 2017 and 2018. In this context, patients who developed ALF were evaluated for LT and, in a pioneering way in the world, the first LT in FA were performed. Objectives: To describe a case series of patients with YF admitted in 2018 at Hospital Felício Rocho (HFR), a tertiary referral hospital for transplantation in the state of Minas Gerais, Brazil. Methods: HFR was appointed as a reference for performing LT in patients with ALF due to YF and developed a protocol: parameters for indicating LT, plasmapheresis, compassionate use of antiviral medications, assessment of coagulopathy, per- and postoperative approach to patients. The database consisted of information from patients with confirmed YF after authorization from the HFR Ethics Committee. Results: 14 patients with confirmed YF were admitted. Eight developed ALF with neurological manifestations that led to death or ALF requiring transplantation. The median (with interquartile range) of laboratory tests in this group revealed: bilirubin (peak) 5.06 mg/dl (2.8-8.3), INR 2.9 (1.4->9.0); factor V 22% (11-29%). The average interval between initial neurological signs and Glasgow Coma Scale <8 was 20 hours (1-60h), and until death 45.5 hours (10-67h). The average jaundice-HE interval was six days. Four patients died without LT, two from septic shock and two from multiple organ failure. Four patients underwent LT. Survival was 50% at five years of follow-up. The modified Clichy criterion (factor V (<50%) and HE grades I/II) was used in successful cases. The two survivors presented infectious complications, such as pneumonia, sepsis of undetermined focus and CMV infection. A liver biopsy was performed on the transplanted patients on the 2nd POD during the hemorrhage approach, and viral recurrence was found on the graft in both. The patient with the highest viral staining on immunohistochemistry showed greater severity in histological findings and died; in contrast, the patient who survived was on compassionate use of sofosbuvir and had lower amounts of virus in the parenchyma and less intense damage to the graft. The other patient who survived LT underwent plasmapheresis and also used sofosbuvir. Discussion: The traditional criteria for indicating LT – King's College and Clichy-Villejuif – were poor predictors of the evolution of patients with ALF due to YF. On the other hand, the “modified Clichy” criteria were useful to indicate LT as they included factor V (more sensitive) in the assessment of coagulopathy and accepted earlier degrees of HE. Neurological manifestations in ALF due to AF were predictors of mortality, but with peculiar characteristics, suggesting that other mechanisms may be associated with liver dysfunction. Reinfection of the graft by the YF virus was universal, suggesting an association between the severity of liver injury and higher viral load. The two patients who survived after LT used sofosbuvir, which may be related to its anti-viral effect. Despite a high mortality rate, the experience proved capable of suggesting changes in conventional procedures that could positively impact the survival of patients transplanted due to YF.